Query verification schemes for cloud-hosted databases: a brief survey. Issue 6 (1st November 2016) - Riaz-ud-Din, Faizal; Zhou, Wanlei; Doss, Robin
Abstract : Database query verification schemes provide correctness guarantees for database queries. Typically such guarantees are required and advisable where queries are executed on untrusted servers. This need to verify query results, even though they may have been executed on one's own database, is something new that has arisen with the advent of cloud services. The traditional model of hosting one's own databases on one's own servers did not require such verification because the hardware and software were both entirely within one's control, and therefore fully trusted. However, with the economical and technological benefits of cloud services beckoning, many are now considering outsourcing both data and execution of database queries to the cloud, despite obvious risks. This survey paper provides an overview into the field of database query verification and explores the current state of the art in terms of query execution and correctness guarantees provided for query results. We also provide indications towards future work in the area.